2021
DOI: 10.1111/cdev.13528
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Components of Sex Differences in Color Preference

Abstract: and Ikunala and Yakel and surrounding villages, who shared their time with us.Competing interests: The authors have no competing interests to declare.Author contributions: JD and MH originated the idea and developed the method. JD collected data in Peru, Vanuatu, and Australia and carried out the analyses. ER translated and collected data in Peru. SLL coordinated and collected data in the Republic of the Congo. KN, RK, and MN organized research in Vanuatu and Australia. MH supervised the project. JD and MH dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 73 publications
(180 reference statements)
0
5
0
Order By: Relevance
“…The mere exposure to co-occurrences of gender and color information in the social environment could provide a basis, which became deeply embedded through statistical learning and language development. For instance, the gender-stereotyped colors of toys and clothing since the early development, that parents commonly dress their baby girls in red/pink and their baby boys in blue/green colors (Auster & Mansbach, 2012;Cohen, 2013;Picariello et al, 1990; LoBue & DeLoache, 2011; Davis et al, 2021), and the widely using of red in female clothing and cosmetics in later life (Frank, 1990), may help to construct the red-female associations. Moreover, gender differences in color preferences, that female tend to prefer reddish colors (Saito, 1996;Hurlbert & Ling, 2007), may also lead to those associations.…”
Section: Discussionmentioning
confidence: 99%
“…The mere exposure to co-occurrences of gender and color information in the social environment could provide a basis, which became deeply embedded through statistical learning and language development. For instance, the gender-stereotyped colors of toys and clothing since the early development, that parents commonly dress their baby girls in red/pink and their baby boys in blue/green colors (Auster & Mansbach, 2012;Cohen, 2013;Picariello et al, 1990; LoBue & DeLoache, 2011; Davis et al, 2021), and the widely using of red in female clothing and cosmetics in later life (Frank, 1990), may help to construct the red-female associations. Moreover, gender differences in color preferences, that female tend to prefer reddish colors (Saito, 1996;Hurlbert & Ling, 2007), may also lead to those associations.…”
Section: Discussionmentioning
confidence: 99%
“…The mere exposure to co-occurrences of gender and color information in the social environment could provide a basis, which became deeply embedded through statistical learning and language development. For instance, the gender-stereotyped colors of toys and clothing since the early development, that parents commonly dress their baby girls in red/pink and their baby boys in blue/green colors (Auster & Mansbach, 2012;Cohen, 2013;Picariello et al, 1990;LoBue & DeLoache, 2011;Davis et al, 2021), and the widely using of red in female clothing and cosmetics in later life (Frank, 1990), may help to construct the strong red-female associations.…”
Section: Discussionmentioning
confidence: 99%
“…Three-or four-year children could classify everyday objects as male or female (e.g., kitchen appliances as female whereas cars as male; Smuda, 2011;Skočajić et al, 2020). With the developmental influence of learned gender roles and gender-typical colors, both children and adults show gender differences in color preference, possibly leading to female preference for pink/reddish colors and male preference for blue/green colors (Cohen, 2013;Hurlbert & Ling, 2007;Picariello et al, 1990;LoBue & DeLoache, 2011;Chiu et al, 2006;Wong & Hines, 2015;Davis et al, 2021). Moreover, color and gender connotation studies showed that people associate gendered words or concepts with colors, such that pink/reddish colors are feminine and blue/green colors are masculine (Cunningham & Macrae, 2011;Chen et al, 2020;Jonauskaite et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kurt & Osueke, (2014) have mentioned the use of appropriate and/or correct colours in the built environment to enhance university students' smooth functionality. Davis et al (2021) have illustrated that colour preference differs by culture. A new study has reported that blue is preferred by most individuals all around the world (Banville, 2022).…”
Section: Colours and University Learning Environmentmentioning
confidence: 99%